Outcomes of Transjugular Intrahepatic Portosystemic Shunt Procedures in a Very-Low-Volume Institution: A Retrospective Single-Center Study - Çelebioğlu, Emre C.; Uludağ, Sena Bozer; Idilman, Ramazan; Gökcan, Hale; Üstüner, Evren; Ellik, Zeynep Melekoğlu; Tanca, Aydan Kansu; Koloğlu, Meltem; Ateş, Ufuk; Güvenir, Sevinç T.; Yilmaz, Volkan; Albayrak, Zehra Işyapan; Alaçayir, İskender; Bilgiç, Sadık (Journal of Gastrointestinal and Abdominal Radiology, 2025)
This study aimed to evaluate the outcomes of transjugular intrahepatic portosystemic shunt (TIPSS) procedures performed in a very-low-volume center over 4 years, focusing on procedural success, complication rates, and clinical effectiveness in managing portal hypertension and related complications.A retrospective analysis was conducted of those who underwent TIPSS at our institution from October 2020 to October 2024. Inclusion criteria were no prior TIPSS or liver surgery and available follow-up data. Data collected included patient demographics, portal hypertension etiology, and procedural details. Success was assessed in technical, hemodynamic, and clinical categories, with complication and readmission rates analyzed.Ten patients (six male, four female; median age 45.5 years, range 12–74) underwent TIPSS between October 2020 and October 2024. TIPSS indications included refractory ascites (40%) and variceal bleeding (60%), with all procedures elective except one emergency case for acute variceal bleeding. Technical success was achieved in 90%, with one unsuccessful shunt placement in a patient due to extensive hepatic vein and vena cava thrombosis. The mean portosystemic pressure gradient (PSG) decreased from 27 ± 3.32 to 8.56 ± 1.74 mm Hg, with hemodynamic success achieved in all patients (PSG ≤ 12 mm Hg). Clinical success was observed with no rebleeding or large-volume paracentesis required within 30 days postprocedure.TIPSS can be effectively performed in a very-low-volume center, yielding favorable outcomes with manageable complications, provided it is conducted by experienced physicians following proper protocols.
Keywords: portal hypertension; portosystemic shunt; encephalopathy; variceal bleeding; ascites